2016
DOI: 10.1016/j.elstat.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic force distribution on an electrodynamic screen

Abstract: The enormous potential of the solar energy harvesting plants for providing clean energy is severely limited by dust accumulation on their optical surfaces. In lieu of the most commonly-practiced manual cleaning method of using high-pressure water jets, the electrodynamic screen (EDS) technology offers an attractive solution for removing dust particles from optical surfaces using electrostatic forces. In this paper, the impacts of different EDS design parameters in the electric field distribution on an EDS have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 29 publications
(33 reference statements)
0
31
0
Order By: Relevance
“…This technology will also solve the problem for solar farms placed in deserts where accumulated dust and sand block the sun light. Experiments performed by MIT have shown that one dust storm can cut power production by 40% …”
Section: Light‐responsive Liquid Crystal Networkmentioning
confidence: 99%
“…This technology will also solve the problem for solar farms placed in deserts where accumulated dust and sand block the sun light. Experiments performed by MIT have shown that one dust storm can cut power production by 40% …”
Section: Light‐responsive Liquid Crystal Networkmentioning
confidence: 99%
“…Humid dust has proved extremely difficult to remove due to the presence of capillary forces between particles mutually and between the particles and the surface . Figure b(2)–(4) shows humid sand grains obtained by adding 10 wt% water.…”
mentioning
confidence: 99%
“…After 3 years of study (2017-2020), Mazumder et al [160] reported that the dust removal efficiency and reflectivity restauration of EDS are both high and that EDS can operate under various temperatures and relative humidity; the authors concluded after an economic analysis that EDS technology is on a commercial level. However, other studies confirmed EDS to be greatly affected by humidity [161,162], Javed and Guo [163] reported a decreasing dust removal efficiency from 22% at RH of 10% to 9% at RH of 80%, and suggested to increase the frequency of EDS device activation (hourly or bi-hourly) in order to improve its cleaning efficiency.…”
Section: Electrodynamic Screens "Eds"mentioning
confidence: 99%